Constitutional amendment on suffrage for 18 year olds in Malaysia - Mohamad Amin, Noor Shuhadawati; Mohd Badrol Afandi, Nor Hafizah; Rajadurai, Mitra Manisha (Lexis Nexis, 2020)
Voting is primarily important not only as a symbol of democracy; it will also determine the government that will run the country. In Malaysia, the Federal Constitution provides the minimum age to pass vote is 21 years old. However, with the recent bill passed in the Parliament, the voting age will be reduced to 18 years old. This paper seeks to investigate the underlying reasons behind the motive to reduce the voting age as some of the positive and negative impacts to reduce the voting age includes 18 years old is the legal age of adulthood in Malaysia by making reference to Thailand and Australia due to the strong resemblance to this country’s legal system. Lastly, this paper also attempts to analyse the constitutional changes that will ensue after the amendment made to the constitution.